اثر الاندماج في سلاسل القيمة العالمية على خلق ودعم المشاريع المقاولاتية في الجزائر 2008/2018 - لـــــميس نصيب; كميليا شريف (My University, 2024)
Through this study, we tried to identify the extent of the impact of integration into global value chains on the creation and support of entrepreneurial projects in Algeria during the period 2008-2018, through a study that included two aspects, a theoretical side and an applied aspect, where the first side was addressed to each of the theoretical framework of the study variables, namely global value chains and entrepreneurial projects, while the second side dealt with the study of the impact of integration into global value chains on the creation and support of entrepreneurial projects, through the collection of statistics. And data for the period from 2008 to 2018. After analyzing and processing these data, the most important results reached were that there is a relationship of impact of foreign value added in total exports on the creation and support of entrepreneurial projects.
Keywords: Keywords: Global value chains; Entrepreneurship; Mergers; Domestic and foreign value added; Exports